2021
DOI: 10.1177/0032258x211016510
|View full text |Cite
|
Sign up to set email alerts
|

The lasting effect of community police academies: Results of a 6-month follow-up

Abstract: Community police academies (CPA) are used by police agencies to educate the public on practices and expand community involvement. Using pre-test, post-test, and follow-up survey data, the current study examines the lasting effects of attending a CPA on citizen knowledge, perceptions, and concerns. Results indicate that participants were more knowledgeable about police practices, perceived officers as more honest and accountable, and expressed lower concerns about use of force and misconduct immediately followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have found that similar types of dialogues have promoted empathy, mutual respect, and trust, with community members feeling they had a stronger voice as a result, 12 and at least one study found positive effects for youth participants. 13 In this research, empathy toward and from officers resulted from explaining their practices and attempting to see community members' points of view, which served to humanize all participants. Trust in these sessions also appears to be an outgrowth of this empathy and in building relationships.…”
Section: Why Use Hypothetical Scenarios?mentioning
confidence: 99%
“…Studies have found that similar types of dialogues have promoted empathy, mutual respect, and trust, with community members feeling they had a stronger voice as a result, 12 and at least one study found positive effects for youth participants. 13 In this research, empathy toward and from officers resulted from explaining their practices and attempting to see community members' points of view, which served to humanize all participants. Trust in these sessions also appears to be an outgrowth of this empathy and in building relationships.…”
Section: Why Use Hypothetical Scenarios?mentioning
confidence: 99%